2019
DOI: 10.1101/585109
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenome-wide meta-analysis of PTSD across 10 military and civilian cohorts identifies novel methylation loci

Abstract: Differences in susceptibility to posttraumatic stress disorder (PTSD) may be related to epigenetic differences between PTSD cases and trauma-exposed controls. Such epigenetic differences may provide insight into the biological processes underlying the disorder. Here we describe the results of the largest DNA methylation meta-analysis of PTSD to date with data from the Psychiatric Genomics Consortium (PGC) PTSD Epigenetics Workgroup. Ten cohorts, military and civilian, contributed blood-derived DNA methylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 69 publications
1
24
0
Order By: Relevance
“…According to iMethyl (accessed Jan 21, 2020), adjacent loci (chr5:373,355 and chr5:373,398) are negatively associated with expression of the AHRR gene in monocytes (p < 5 × 10 -6 ). Additionally, as reported in Smith et al, methylation at this locus is associated with lower kynurenine and kynurenic acid [17]. Based on the examination of the impact of the smoking score and our follow-up analyses using the score and smoking, we conclude that our data are consistent with a PTSD effect which is independent of the association with smoking.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…According to iMethyl (accessed Jan 21, 2020), adjacent loci (chr5:373,355 and chr5:373,398) are negatively associated with expression of the AHRR gene in monocytes (p < 5 × 10 -6 ). Additionally, as reported in Smith et al, methylation at this locus is associated with lower kynurenine and kynurenic acid [17]. Based on the examination of the impact of the smoking score and our follow-up analyses using the score and smoking, we conclude that our data are consistent with a PTSD effect which is independent of the association with smoking.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are highly relevant to the epigenetics of PTSD because PTSD samples, especially from veteran cohorts, tend to have an elevated prevalence of cigarette smoking relative to the general population [23]. The AHRR locus cg05575921 that was associated with PTSD in the Smith et al EWAS [17] was also highly significant in both the Joehanes et al EWAS of smoking [21] and the Li et al EWAS of smoking [22], and in the latter, was the most significant locus. Based on this, Smith et al also performed analyses stratified by smoking status and found that the association between PTSD and cg05575921 was strongest among non-smokers suggesting an association between PTSD and AHRR independent of smoking.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The most recent meta-analyses of GWAS data from the PGC PTSD workgroup (n~200,000) revealed numerous significant variants and quantified the molecular heritability of PTSD (Nievergelt et al, 2019). Collaborative efforts from the PGC have led to progress on finding epigenome-wide significant sites related to risk for PTSD (Smith et al, 2019). Systems biology advances, in large part driven by complex data-driven agnostic analytic approaches to multidimensional data (Neylan, Schadt, & Yehuda, 2014), are developing and hold promise and will be needed to co-analyse data on multiple omics platforms simultaneously.…”
Section: Ten Years Of Progress In Genomicsmentioning
confidence: 99%
“…All subjects were free of a PTSD diagnosis at pre-deployment and had CAPS scores ≤ 25. After return from a ~7-months deployment period, PTSD cases (following the DSM-IV full or partially stringent diagnosis [11,12]) were selected either at the three-or the six-month follow-up visit, based on when these subjects had their highest recorded CAPS scores. Subsequently, controls were frequency matched to the selected cases for age, ancestry, and time of post-deployment visit.…”
Section: Marine Resiliency Studymentioning
confidence: 99%